FRI0250 Coronary CT-Angiography Reveals the Extent of Coronary Artery Disease in Takayasu Arteritis. (9th June 2015) - Tombetti, E.; Khamis, R.; Gopalan, D.; Kiprianos, A.; Ariff, B.; Mason, J.C.
Abstract : Background: Cardiovascular complications imply a poor prognosis in Takayasu arteritis (TA). TA is a pro-atherogenic condition, but the relationship between vasculitis and atherosclerosis remains elusive. Coronary artery disease (CAD) in TA may be i) vasculitic, ii) atherosclerotic or iii) due to pauci-inflammatory remodelling after revascularisation. Up to 25% of TA patients have evidence of silent myocardial scarring, suggesting a higher prevalence of myocardial ischemia than previously recognized. Thus, we established a coronary CT-angiography (cCTA) screening programme in a well characterized cohort of 50 TA patients. Objectives: To assess the sensitivity of cCTA in identifying CAD in TA and to determine whether it can distinguish coronary arteritis from atherosclerotic CAD. Methods: We initially selected 50 TA patients with known/suspected CAD or involvement of the ascending aorta for screening. Analysis: i) clinical and laboratory data (disease extent, activity, inflammatory burden, medications, traditional atherosclerotic risk factors), ii) MR angiography-based assessment of disease burden and extent, iii) cCTA. Two independent assessors reviewed the images. The total coronary calcium score and coronary lesions were evaluated and the latter characterized by severity (% stenosis), length, spatial distribution, relationship with previous interventional procedures and presence of calcific deposits. Results: To date, 39 scans have been performed in 35 TA patients (31 women). Median age (interquartile range, IQR) was 45 (33-55) years. 18/35 (51%) patients had detectable CAD. Of these 18 patients with positive scans, 9 (50%) were asymptomatic for CAD, while 11 (61%) had evidence of ascending aortitis. The left main stem, the left anterior descending, circumflex, right coronary and posterior descending arteries were involved in 7, 11, 9, 11 and 2 patients respectively (39%, 61%, 50%, 61% and 11% of TA patients with CAD). 13/18 (72%) patients with CAD had multi-vessel coronary disease. 6/18 (33%) patients had involvement of only the coronary ostia/proximal coronary tree, while 12/18 (67%) had more diffuse involvement. Three patients had undergone coronary revascularisation: 6 bypass grafts in total (2 venous grafts and 4 arterial grafts), and 2 bare-metal stents. None of the procedures had failed and there were no signs of local vascular remodelling. Calcium score data were not available for 4 patients (all of whom have CAD). Mean and median (IQR) calcium scores for the whole cohort were 28 and 0 (0-25) respectively. 6 patients with CAD had a calcium Agatston score of 0. Patients with ostial/proximal arterial involvement (suggestive of coronary arteritis) had a trend towards lower calcium scores (Figure 1 ). 5 of these patients had a calcium Agatston score of 0. Correlation of cCTA with clinical and MR arterial injury data is ongoing. Conclusions: CAD is frequent in TA, is an important cause of morbidity, and is often asymptomatic and overlooked. Typical vasculitic CAD results in ostial/proximal lesions and does not appear to increase coronary calcium score. However, further analysis to distinguish the atherosclerotic and vasculitic patterns of CAD in TA is ongoing. Our data suggest that the threshold for the use cCTA in TA should be reduced and cCTA should be considered in all patients. Disclosure of Interest: None declared